A constructivist grounded theory exploration of Mindfulness for Healthcare Professional students. (February 2023) - Braun, Sarah Ellen; Mladen, Samantha; Crawford, MaryKate; Edwards, Sarah; Kinser, Patricia
Abstract: Background and purpose: To better understand the effects of an intervention, Mindfulness for Healthcare Professional (MIHP), and how it may improve healthcare professional student (HCP) functioning, a constructivist grounded theory exploration was conducted. Materials and methods: Ten participants with the lowest or highest changes on quantitative measures of burnout and perceived stress at the end of MIHP were interviewed at a long-term follow-up. A theoretical framework was developed from the resultant themes to describe the mechanisms by which MIHP had effects on work-relevant functioning. Results: Three overarching themes emerged as mechanisms of change both from their presence in those participants reporting an improvement in stress and their missingness from those participants who reported no change: developing a mindfulness practice, integrating practice into daily life, and enhanced awareness. These mechanisms led to optimized work-relevant functioning: 1) emotional competencies, including nonjudgement, emotion regulation, and burnout prevention; and 2) patient-centered care, including improved listening, patience, and efficiency at work. Conclusion: The resultant framework is discussed in the context of previous literature on MIHP and mindfulness theory more broadly. Implications for future disseminations of MIHP encourage the use of group interventions with emphasis on developing at-home practice and informal mindfulness integrated into daily work. Highlights: Following a mindfulness intervention, interdisciplinary healthcare students reported a wide range of mindfulness integration. Mindfulness had positive effects on healthcare professional student functioning through integration into daily living. Developing a Habit led to Integration via Awareness, which then improved Emotional Competencies and Patient-Centered Care. This relationship was not linear, but represented by interconnected changes, dependent upon the level of Integration achieved.